2009
DOI: 10.1094/phyto-99-4-0462
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Phylogenetic Diversity of Fusarium avenaceum Pathogenic on Lisianthus

Abstract: Fusarium avenaceum is a globally distributed fungus commonly isolated from soil and a wide range of plants. Severe outbreaks of crown and stem rot of the flowering ornamental, lisianthus (Eustoma grandiflorum), have been attributed to F. avenaceum. We sequenced portions of the translation elongation factor 1-alpha (tef) and beta-tubulin (benA) protein coding genes as well as partial intergenic spacer (IGS) regions of the nuclear ribosomal genes in 37 Fusarium isolates obtained from lisianthus and other host pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
1
35
2
Order By: Relevance
“…We detected several OTUs identified as F. avenaceum, revealing intraspecific diversity. This species has previously been reported to harbor high diversity (71). Up to eight OTUs were present in the same sample, indicating that species-specific PCR assays may soon become laborious when attempting to capture Fusarium diversity in cereals.…”
Section: Discussionmentioning
confidence: 93%
“…We detected several OTUs identified as F. avenaceum, revealing intraspecific diversity. This species has previously been reported to harbor high diversity (71). Up to eight OTUs were present in the same sample, indicating that species-specific PCR assays may soon become laborious when attempting to capture Fusarium diversity in cereals.…”
Section: Discussionmentioning
confidence: 93%
“…Fusarium avenaceum is known to harbor high intra-specific diversity (Nalim et al, 2009). One of the F. avenaceum OTUs dominated with 24% of the reads followed by three minor ones (<2% of the reads).…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with results of several previous studies. Nalim et al (2009) demonstrated the absence of phylogenetic separation between F. avenaceum isolates from lisianthus and those from other hosts and suggested that the ability to cause diseases on this ornamental occurs broadly within the species. Harrow et al (2010) revealed high intraspecific polymorphism of TEF1α and β-TUB sequences between F. avenaceum isolates from cereal and grassland sites of New Zealand but did not find strict phylogenetic structure with relation to host and indicated capability of this species to infect a wide range of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising target used for phylogenetic analysis of enniatinproducing Fusarium species is enniatin synthetase gene (Stępień and Waśkiewicz, 2013). There were several studies of intraspecific diversity of F. avenaceum Nalim et al, 2009) and its relationship with other species (Harrow et al, 2010;Yli-Mattila et al, 2002b, 2004b. At the same time, there is little information on genetic variation between isolates of F. avenaceum and closest relatives from Russia, especially Siberia and Far East.…”
Section: Introductionmentioning
confidence: 99%